"Dollars and Scents: Alternative Currency Acceptance in Artisanal Markets in Guadalajara Mexico"1. Issue 1 (March 2014) - Pisani, Michael J.; Pérez, Luis Fernando Cruz; Corona, María Nitzayé Hernández; Godínez, Jesús Eduardo
Abstract The recent globalization of tourism has connected international consumer and local artisan directly and more intensively. As foreign buyer and artisan seller interact, a variety of payment options and mechanisms may be considered, including cash transfers in the buyer's home currency. In this article, we report the findings of a June 2012 survey (n = 97) of U.S. dollar acceptance within inland artisanal markets in Guadalajara, Mexico. Even though the Mexican regulatory environment for U.S. dollar usage in Mexico has thickened since 2010, we find that a majority of Mexican firms located in traditional artisanal zones in the Guadalajara metropolitan area willingly accept the U.S. dollar in retail transactions. These small‐scale artisanal enterprises accept U.S. dollars in payment, on occasion substituting the U.S. dollar in place of the local Mexican peso for transactions, because U.S. dollar acceptance drives higher sales volumes and the opportunity to earn a premium on the currency exchange. We find that the determinants of Mexican firm‐level U.S. dollar acceptance include business maturity, higher levels of foreign patronage, and focused artisanal production.